Studies on vegetable oils as fuel in CI engines - GEORGE MATHEW NEERACKAL JOE JOE L. BOVAS SAREENA K. V; Dr. Shaji James P (Guide) (Tavanur 2005 Kelappaji College of Agricultural Engineering and Technology)
Studies on vegetable oils as fuel in CI engines
Studies on vegetable oils as fuel in CI engines